Inflammation down regulates stromal cell-derived factor 1α in the early phase of pulpitis. (October 2022) - Leng, Sha; Liu, Linyi; Xu, Weizhe; Yang, Fan; Du, Jing; Ye, Ling; Huang, Dingming; Zhang, Lan
Highlights: Pulpal inflammation played a bidirectional role in SDF-1α expression. The decrease of SDF-1α expression in the early stage of pulpitis attenuated DPC migration. TNFR2 and AIP1 were required for Pg.LPS to activate JNK/c-Jun (Ser63) pathway in DPCs. Abstract: The key to prevent pulp necrosis in the early stage of pulpitis is to promote tissue repair, which begins with cell migration. Stromal cell-derived factor 1α (SDF-1α) has been proven to promote cell migration. Related research has so far concentrated on the biological effects of SDF-1α while its expression in pulpitis is still unclear. We investigated the effect of inflammation on SDF-1α in dental pulp and the underlying regulatory mechanisms. First, rat pulpitis models were established by exposing pulp. SDF-1α was decreased on the 3rd day but increased on the 7th day. Next, lipopolysaccharide from Porphyromonas gingivalis ( Pg .LPS) was applied to dental pulp cells (DPCs). Within 24 h, SDF-1α decreased, but after 48 h, it steadily increased. Similarly, SDF-1α expression in human chronic pulpitis tissues was also increased. To investigate the effect of altered SDF-1α on DPC migration, cell supernatants collected following Pg .LPS treatment were utilized to stimulate DPCs, and the number of migrated cells was correlated with changes in SDF-1α secretion. Finally, we explored the regulatory mechanisms of SDF-1α down-regulation in the early phase of pulpitis. Within 24 h, JNK/c-Jun pathway was activated in DPC inflammation. When JNK pathway was suppressed, SDF-1α rose. Furthermore, tumor necrosis factor receptor 2 (TNFR2) and apoptosis signal-regulated kinase-interacting protein 1 (AIP1) were up-regulated. Knockdown of them abolished Pg .LPS-induced activation of JNK and c-Jun(Ser63) and significantly enhanced SDF-1α. Our findings indicated that in the early phase of pulpitis, inflammation suppressed SDF-1α by up-regulating TNFR2 and AIP1, which activated JNK/c-Jun(Ser63) pathway.